2013
DOI: 10.1530/erc-13-0082
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid cancer and co-occurring RET mutations in Hirschsprung disease

Abstract: The objective of this study was to assess the occurrence of thyroid cancer and co-occurring RET mutations in a population-based cohort of adult Hirschsprung disease (HD) patients. All 156 patients operated for HD in a tertiary center during 1950-1986 were followed for thyroid malignancies up to 2010 through the nationwide Finnish Cancer Registry. Ninety-one individuals participated in clinical and genetic screening, which included serum calcitonin and thyroid ultrasound (US) with cytology. Exons 10, 11, 13, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…exon 10), such as C620R, it has been classically reported that HSCR develops in up to 7% of carriers. Since the initial report, other Y791F-carrier HSCR cases with no evidence of MTC have been reported, raising the question as to whether this variant is actually involved in tumourigenesis ( Virtanen et al . 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…exon 10), such as C620R, it has been classically reported that HSCR develops in up to 7% of carriers. Since the initial report, other Y791F-carrier HSCR cases with no evidence of MTC have been reported, raising the question as to whether this variant is actually involved in tumourigenesis ( Virtanen et al . 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, medullary thyroid carcinoma incidence among Hirschsprung disease patients varies between 2.5% and 5%, with all activating mutations located in exon 10. 79 As it was not possible to perform functional studies to assess the pathogenicity of this specific variant, it was classified as a VUS and the recommendation for this case would be to follow it as a potential MEN2 case.…”
Section: Genetic Screeningmentioning
confidence: 99%
“…However, no clinical data from the deceased sisters were available, as they had lived abroad, and it was not apparent whether the deceased sisters had been tested for RET Y791F carrier status . To the best of our knowledge, the remaining studies on the RET Y791F variant have been centered around index cases, with no more than one occurrence of MTC in a proven RET Y791F carrier per family, enabling noncausative occurrences of RET Y791F in patients with sporadic MTC to have been attributed an unwarranted pathogenic significance . Further compounding this, a recent retrospective German study found no age‐related progression of MTC in RET Y791F carriers, which would otherwise often be expected in hereditary disease …”
Section: Discussionmentioning
confidence: 99%